2011
DOI: 10.1021/es202445w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aqueous Fe(II) on Arsenate Sorption on Goethite and Hematite

Abstract: Biogeochemical iron cycling often generates systems where aqueous Fe(II) and solid Fe(III) oxides coexist. Reactions between these species result in iron oxide surface and phase transformations, iron isotope fractionation, and redox transformations of many contaminant species. Fe(II)-induced recrystallization of goethite and hematite has recently been shown to cause the repartitioning of Ni(II) at the mineral-water interface, with adsorbed Ni incorporating into the iron oxide structure and preincorporated Ni r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 66 publications
(87 reference statements)
3
39
0
Order By: Relevance
“…Arsenate adsorption was reported to decrease the surface zeta potential of the soils [16]. In another study of As(V) and Fe(II) adsorption on goethite, As(V) adsorption was also found to shift the surface potential to a more negative value and enhanced Fe(II) adsorption [34], which is consistent with our observation. Moreover, the different adsorption procedures result in different Cd sorption amount.…”
Section: Adsorption Dynamicssupporting
confidence: 91%
“…Arsenate adsorption was reported to decrease the surface zeta potential of the soils [16]. In another study of As(V) and Fe(II) adsorption on goethite, As(V) adsorption was also found to shift the surface potential to a more negative value and enhanced Fe(II) adsorption [34], which is consistent with our observation. Moreover, the different adsorption procedures result in different Cd sorption amount.…”
Section: Adsorption Dynamicssupporting
confidence: 91%
“…As with haematite, Frierdich et al [36] observed incorporation of Ni 2 + into Fe 2 + -exposed goethite using XAS, with nickel in a co-ordination environment similar to that of nickel-doped goethite. In contrast, XAS indicated that As 5 + remained sorbed or precipitated as ferrous arsenate rather than being incorporated in goethite during Fe 2 + -induced recrystallization [56]. In contrast, XAS indicated that As 5 + remained sorbed or precipitated as ferrous arsenate rather than being incorporated in goethite during Fe 2 + -induced recrystallization [56].…”
Section: Goethitementioning
confidence: 87%
“…For example, the incorporation of uranium in iron oxides has been suggested to make the uranium less resistant to oxidative mobilization [5,50]. [7,46,56]). [67]), as well as predicting the release of metals such as arsenic into water (e.g.…”
Section: Closing Remarksmentioning
confidence: 99%
“…At the same time, it is important to note that under the reducing conditions found in anoxic portions of landfills, iron oxides may be reduced, and release bound metals in the system (Charlatchka and Cambier, 2000;Ghosh et al, 2004). Iron cycling and metal sorption occurs at the interface for trace metals such as Pb and As (Catalano et al, 2011;Neumann et al, 2013).…”
Section: Metal Forms In the Paint Wastementioning
confidence: 99%